Swedish occupational therapists’ views and experiences regarding use of the ADL-taxonomy in clinical practice. - Hu,Claire (2023)
Background: The ADL-taxonomy as an assessment instrument shows high validity and reliability in the clinical research, but there is no study about occupational therapists’ experiences of using the ADL-taxonomy in clinical practice. It is important to study the users’ experiences and views to improve implementation of evidence-based methods such as the ADL-taxonomy. Aim: The aim of this study is to explore Swedish occupational therapists’ views and experiences regarding use of the ADL-taxonomy as an assessment instrument in clinical practice. Method: Qualitative design with semi-structured interviews was used. Inductive content analysis was used to analyze the collected data with five licensed Swedish occupational therapists . Results: The analysis resulted in two main categories: (1) Trying to be professional and (2) Depending on the environmental impact. The occupational therapists considered use of the ADL-taxonomy to be a positive aspect in professional development, however their performances were strongly affected by the enviormental factors in clinical practice. Conclusion: Using evidence-based assessment methods such as the ADLtaxonomy is important for Swedish occupational therapists’ professional development. However, whether to choose the ADL-taxonomy and how to use it depend on the specific patient and the environmental factors. To encourage the implementation of evidence-based methods in clinical practice, healthcare organizations need to make an effort to build supportive work environments for practitioners.
Keywords: Activities of daily living (ADL); assessment of ADL; environmental factors; professional development; standardized instrument; work environment.